Comparison on customer perception on Goods and Services Tax (GST) of lower and middle income earners in Kota Bharu and Kuala Terengganu / Idahazwani Junus and Nur Hidayah Zainuddin - Junus, Idahazwani; Zainuddin, Nur Hidayah (2014)
Good and Services Tax (GST) is a consumption tax imposed to taxpayers. Many developed countries such as the United States, United Kingdom, Singapore and Australia had been implementing the GST. At the early stage of the introduction of GST, many people from various income classes would be disagree as they perceived that the prices of the basics needs as well as many items would increase. The national budget of Malaysia 2014 had been tabled in Parliament on 27 October 2013 proposing that GST would be implemented commencing on 1 April 2015 at 6% which is 2% higher than expected. Many people especially from lower income earners were afraid of their purchasing capabilities when GST is implemented. Therefore, this paper aims to examine comparison of the consumer readiness, knowledge, awareness and perception of GST in Kota Bharu and Kuala Terengganu if it is implemented in Malaysia. The paper will focus on middle and lower income as this group of people would be affected more compared to other income earners group. This paper involves 200 respondents; 100 respondents from Kota Bharu and other 100 respondents from Kuala Terengganu.